Anti-crack asphalt concrete material and preparation method thereof

By adding reinforced fillers of modified lignin, diatomaceous earth and hydrotalc to asphalt concrete materials, as well as composite aerogel prepared by reaction of acryloyl chloride and 2,4-dihydroxybenzophenone, the problems of asphalt concrete materials being prone to cracking, poor low temperature resistance and poor UV aging resistance are solved, and the crack resistance and service life of the material are significantly improved.

CN119661123AActive Publication Date: 2025-03-21NINGBO DONGXING ASPHALT PROD CO LTD

Patent Information

Application Number
CN202411842509.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

During the preparation process, existing asphalt concrete materials are prone to cracking, poor low temperature resistance and poor UV aging resistance, resulting in a shortening of service life.

Method used

By adding reinforcement filler and composite aerogel, the reinforcement filler consists of modified lignin, diatomaceous earth and hydrotalcite, and cross-linked with silane coupling agent. The composite aerogel is prepared by reaction of acryloyl chloride and 2,4-dihydroxybenzophenone to form a material with excellent thermal insulation properties and a three-dimensional network structure.

Benefits of technology

The crack resistance, service life and UV aging resistance of asphalt concrete materials are significantly improved, and the filler improves the dispersion and crack resistance of the matrix through synergistic action. The three-dimensional mesh structure of the composite aerogel enhances the toughness and thermal insulation effect of the matrix.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005188273800000131
    Figure BDA0005188273800000131
Patent Text Reader

Abstract

The invention relates to the technical field of asphalt concrete, and discloses an anti-crack asphalt concrete material and a preparation method thereof. According to the asphalt concrete material disclosed by the invention, by adding the reinforcing filler and the composite aerogel, the crack resistance, the service life and the ultraviolet aging resistance of a matrix are remarkably improved; wherein the reinforcing filler is based on the synergistic effect among modified lignin, diatomite and hydrotalcite, the compatibility among modified lignin, diatomite and hydrotalcite is improved by utilizing a silane coupling agent, and the dispersity of the reinforcing filler in a matrix is improved, so that the crack resistance of the matrix is improved, the service life of the matrix is prolonged, and the ultraviolet resistance of the matrix is improved; the composite aerogel has excellent heat insulation performance and a three-dimensional network structure, and the crack resistance of the matrix can be improved through the synergistic effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of asphalt concrete, and in particular to an anti-cracking asphalt concrete material and a preparation method thereof. Background Art

[0002] Asphalt concrete material is a composite material used in road construction. It is mainly composed of asphalt, aggregate, filler and various additives. It has the advantages of good adhesion, strong adaptability, convenient construction, low maintenance cost and good environmental adaptability. Therefore, it can be widely used in the construction of transportation infrastructure such as roads, airport runways and parking lots. It is one of the indispensable materials for modern transportation construction.

[0003] However, it is difficult to prepare ideal asphalt concrete when preparing asphalt concrete materials. Asphalt concrete is prone to cracking, has poor low temperature resistance, and has poor UV aging resistance, which greatly reduces the service life of asphalt concrete pavement. In order to solve the cracking problem of asphalt concrete materials, fiber materials (such as polypropylene fiber, plant fiber, glass fiber, etc.), rubber powder, polymer modifiers and other materials are generally added to improve the crack resistance of asphalt concrete, but the crack resistance effect is limited. Therefore, researchers need to develop an asphalt concrete material with excellent crack resistance, UV resistance and service life. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides an anti-cracking asphalt concrete material and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] An anti-cracking asphalt concrete material comprises the following raw materials in parts by weight: 8-16 parts of asphalt, 60-80 parts of coarse aggregate, 25-45 parts of fine aggregate, 5-9 parts of fly ash, 5-12 parts of reinforcing filler, and 3-7 parts of composite aerogel;

[0007] The reinforcing filler is prepared by the following steps:

[0008] Step A1, methacrylic acid and 1,6-heptadien-4-ol are mixed and stirred uniformly, 98 wt% concentrated sulfuric acid is added, and the temperature is raised to 60-80° C., and the reaction is carried out at a pressure of 0.2-0.3 MPa for 2.5-4.5 hours, and vacuum distillation, cooling, and filtering are performed to obtain diene methacrylate;

[0009] Step A2, calcium chloride is evenly dispersed in dimethyl sulfoxide, and enzymatic lignin is added and stirred for 10 minutes, ultrasonic treatment is performed for 15 minutes, and then diene methacrylate and 30 wt% hydrogen peroxide are slowly added, and the temperature is raised to 35-45° C., and the reaction is stirred for 16-24 hours, and then deionized water is added and stirred for 10-20 minutes, and filtered, washed, and dried to obtain terminal double-bond lignin;

[0010] Step A3, under nitrogen conditions, disperse the terminal double-bond lignin in tetrahydrofuran evenly, then slowly introduce hydrogen sulfide gas, react at 45-55° C. for 1-2 days, filter, wash, and dry to obtain modified lignin;

[0011] Step A4, the modified lignin, diatomaceous earth and hydrotalcite are mixed and ground, and then a silane coupling agent, deionized water and ethanol are added, mixed and stirred at 35-45° C. for 2-4 hours, allowed to stand for 2 hours, filtered and dried to obtain a reinforcing filler;

[0012] Further, in step A1, the usage ratio of methacrylic acid, 1,6-heptadien-4-ol and concentrated sulfuric acid is 0.1-0.2 mol: 0.105-0.021 mol: 0.43-0.86 g;

[0013] Further, in step A2, the usage ratio of calcium chloride, dimethyl sulfoxide, enzymatic lignin, diene methacrylate, hydrogen peroxide and deionized water is 3.1-6.2 g: 200 mL: 5-10 g: 0.012-0.024 mol: 1.5-3 g: 200 mL;

[0014] Further, in step A3, the ratio of terminal double bond lignin to tetrahydrofuran is 0.5-2 g: 20 mL;

[0015] Further, in step A4, the usage ratio of modified lignin, diatomaceous earth, hydrotalcite, silane coupling agent, deionized water and ethanol is 20-50 g: 5-15 g: 5-10 g: 2-5 g: 20 mL: 180 mL;

[0016] Furthermore, the silane coupling agent in step A4 is one of KH550, KH560 or KH570.

[0017] The composite aerogel is prepared by the following steps:

[0018] Step B1, slowly add the 2,4-dihydroxybenzophenone solution to the acryloyl chloride solution in an ice water bath, and stir continuously for 5-10 minutes, then warm to room temperature, stir and react for 4-6 hours, then add deionized water for washing, separate the liquid, rotary evaporate to 50 mL, then add methanol and stir for 10 minutes, then rotary evaporate to 50 mL, let stand for 24 hours, filter, redisperse the filter cake in dichloromethane, then add petroleum ether and stir vigorously for 10-20 minutes, filter, and dry to obtain a terminal double bond product;

[0019] Step B2, under nitrogen conditions, KH550 is evenly dispersed in methanol, the terminal double bond product is slowly added, and stirred at room temperature for 30 minutes, and then the reaction is carried out in a 25°C oil bath at a constant temperature for 3.5-4.5 hours, and the mixture is distilled under reduced pressure to obtain the grafted modified silane;

[0020] Step B3, dispersing the grafted modified silane and KH550 in ethanol, recorded as solution A; dispersing tetraethyl orthosilicate in ethanol, and adjusting the pH of the solution to 2-3, slowly adding solution A, stirring at room temperature for 8-12 hours, adjusting the pH of the system to 7-8, vigorously stirring for 5-10 minutes, transferring to a mold and standing to form a gel, then aging for 12 hours, washing, and freeze-drying to obtain a composite aerogel;

[0021] Further, in step B1, the usage ratio of acryloyl chloride solution, 2,4-dihydroxybenzophenone solution, deionized water, methanol, dichloromethane and petroleum ether is 100 mL: 100 mL: 200 mL: 50 mL: 50 mL: 200 mL;

[0022] Further, in step B1, the acryloyl chloride solution is prepared by mixing acryloyl chloride and dichloromethane in a dosage ratio of 0.1-0.3 mol: 100 mL, and the 2,4-dihydroxybenzophenone solution is prepared by mixing 2,4-dihydroxybenzophenone, triethylamine and dichloromethane in a dosage ratio of 0.05-0.2 mol: 0.1-0.3 mol: 100 mL;

[0023] Further, in step B2, the usage ratio of KH550, methanol and terminal double bond product is 4.68-9.37 mL:10 mL:5.6-11.2 g;

[0024] Further, in step B3, the dosage ratio of tetraethyl orthosilicate, ethanol and solution A is 11-22 mL: 20 mL: 20 mL;

[0025] Furthermore, the usage ratio of the grafted modified silane, KH550 and ethanol in solution A of step B3 is 3-6 g: 1.5-2.5 mL: 20 mL.

[0026] A method for preparing a crack-resistant asphalt concrete material comprises the following steps:

[0027] Step S1, weighing raw materials by weight, mixing and stirring the coarse aggregate, fine aggregate, fly ash and reinforcing filler to obtain a mixed dry material;

[0028] Step S2, heating the asphalt to 140-170° C., stirring continuously, and sequentially adding the mixed dry material and the composite aerogel, mixing evenly, to obtain the anti-cracking asphalt concrete material.

[0029] Beneficial effects of the present invention:

[0030] The asphalt concrete material in the present application significantly improves the crack resistance, service life and UV aging resistance of the matrix by adding reinforcing fillers and composite aerogels; wherein, the reinforcing fillers are based on the synergistic effect between modified lignin, diatomaceous earth and hydrotalcite, and the silane coupling agent is used to improve the compatibility between each other, thereby improving the dispersibility of the reinforcing fillers in the matrix, thereby improving the crack resistance, service life and UV resistance of the matrix; the composite aerogel has excellent thermal insulation properties and a three-dimensional network structure, which can synergistically improve the crack resistance of the matrix.

[0031] In the reinforcing filler, methacrylic acid and 1,6-heptadien-4-ol are firstly used to synthesize diene methacrylate by esterification reaction; diene methacrylate is then used to undergo free radical copolymerization with enzymatic lignin to obtain terminal double-bond lignin; the double bonds in the terminal double-bond lignin are then reacted with hydrogen sulfide gas to obtain modified lignin containing thiol groups; finally, the modified lignin, diatomaceous earth and hydrotalcite are mixed and ground, and cross-linked by silane coupling agent to obtain reinforcing filler. The reinforcing filler is based on the synergistic effect between modified lignin, diatomaceous earth and hydrotalcite, and the silane coupling agent is used to improve the compatibility between them, improve the dispersibility of the reinforcing filler in the matrix, and thus improve the matrix's crack resistance, service life and UV resistance; among them, the modified lignin can use its fiber characteristics to play a reinforcing role in the matrix, improve the shear strength and compressive strength of the asphalt concrete material, and reduce the generation and expansion of cracks; the modified lignin also contains a large number of thiol groups, which can chelate metal ions (such as Fe 3+ , Ca 2+ Mg 2+ The diatomaceous earth and hydrotalcite both have high specific surface area and porosity, and can effectively absorb harmful substances in asphalt concrete, reduce the aging and deterioration of asphalt, and thus reduce the occurrence of problems such as cracking and deformation. In addition, the reinforcing filler in the matrix can also improve the matrix's resistance to ultraviolet aging through physical shielding, thereby reducing the cracking and peeling of asphalt concrete materials.

[0032] In the composite aerogel, acryloyl chloride and 2,4-dihydroxybenzophenone are reacted to obtain a terminal double bond product; the terminal double bond product is then reacted with KH550 to obtain a grafted modified silane; finally, the grafted modified silane, KH550 and tetraethyl orthosilicate are used as raw materials to synthesize the composite aerogel. The composite aerogel in the matrix can significantly improve the thermal insulation effect of the matrix, reduce the thermal expansion and contraction of asphalt concrete during temperature changes, thereby reducing cracks caused by temperature stress. At the same time, the three-dimensional network structure of the aerogel can also enhance the toughness of the matrix, making it resistant to cracking under external forces, further improving the crack resistance of the matrix; in addition, the aerogel also introduces a benzophenone structure with ultraviolet absorption, which can reduce the cracking of the matrix caused by ultraviolet aging. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1: The reinforcing filler is prepared by the following steps:

[0035] Step A1, 0.1 mol of methacrylic acid and 0.105 mol of 1,6-heptadien-4-ol were mixed and stirred uniformly, 0.43 g of 98 wt% concentrated sulfuric acid was added, and the temperature was raised to 60° C., and the mixture was reacted at a pressure of 0.2 MPa for 2.5 h, and the mixture was distilled under reduced pressure, cooled, and filtered to obtain diene methacrylate;

[0036] Step A2, 3.1 g of calcium chloride was evenly dispersed in 200 mL of dimethyl sulfoxide, 5 g of enzymatic lignin was added and stirred for 10 min, ultrasonic treatment was performed for 15 min, and then 0.012 mol of diene methacrylate and 1.5 g of 30 wt% hydrogen peroxide were slowly added, and the temperature was raised to 35° C., and the reaction was stirred for 16 h, and then 200 mL of deionized water was added and stirred for 10 min, filtered, washed, and dried to obtain terminal double-bond lignin;

[0037] Step A3, under nitrogen conditions, 0.5 g of terminal double-bond lignin was evenly dispersed in 20 mL of tetrahydrofuran, and then hydrogen sulfide gas was slowly introduced, and the mixture was reacted at 45° C. for 1 day, filtered, washed, and dried to obtain modified lignin;

[0038] Step A4: 20 g of modified lignin, 5 g of diatomaceous earth and 5 g of hydrotalcite were mixed and ground, and then 2 g of silane coupling agent KH550, 20 mL of deionized water and 180 mL of ethanol were added, mixed and stirred at 35° C. for 2 h, allowed to stand for 2 h, filtered and dried to obtain a reinforced filler.

[0039] The composite aerogel is prepared by the following steps:

[0040] Step B1, slowly add 100 mL of acryloyl chloride solution to 100 mL of 2,4-dihydroxybenzophenone solution in an ice water bath, and stir continuously for 10 min, then heat to room temperature, stir and react for 6 h, then add 200 mL of deionized water for washing and separation, rotary evaporate to 50 mL, then add 50 mL of methanol and stir for 10 min, then rotary evaporate to 50 mL, let stand for 24 h, filter, redisperse the filter cake in 50 mL of dichloromethane, then add 200 mL of petroleum ether and stir vigorously for 20 min, filter, and dry to obtain a terminal double bond product, the acryloyl chloride solution is prepared by mixing acryloyl chloride and dichloromethane in a dosage ratio of 0.3 mol: 100 mL, and the 2,4-dihydroxybenzophenone solution is prepared by mixing 2,4-dihydroxybenzophenone, triethylamine and dichloromethane in a dosage ratio of 0.2 mol: 0.3 mol: 100 mL;

[0041] Step B2, under nitrogen conditions, 9.37 mL of KH550 was evenly dispersed in 10 mL of methanol, 11.2 g of the terminal double bond product was slowly added, and stirred at room temperature for 30 min, and then the mixture was kept in a 25° C. oil bath for 4.5 h, and distilled under reduced pressure to obtain the grafted modified silane;

[0042] Step B3, 6 g of grafted modified silane and 2.5 mL of KH550 were dispersed in 20 mL of ethanol, recorded as solution A; 22 mL of tetraethyl orthosilicate was dispersed in 20 mL of ethanol, and the pH of the solution was adjusted to 3, 20 mL of solution A was slowly added dropwise, stirred at room temperature for 12 h, the pH of the system was adjusted to 8, and after vigorous stirring for 10 min, it was transferred to a mold and allowed to stand to form a gel, and then aged for 12 h, washed, and freeze-dried to obtain a composite aerogel.

[0043] Example 2: The reinforcing filler is prepared by the following steps:

[0044] Step A1, 0.15 mol of methacrylic acid and 0.16 mol of 1,6-heptadien-4-ol were mixed and stirred uniformly, 0.65 g of 98 wt% concentrated sulfuric acid was added, and the temperature was raised to 70° C., and the mixture was reacted at a pressure of 0.25 MPa for 3.5 h, and the mixture was distilled under reduced pressure, cooled, and filtered to obtain diene methacrylate;

[0045] Step A2, 4.7 g of calcium chloride was evenly dispersed in 200 mL of dimethyl sulfoxide, 7.5 g of enzymatic lignin was added and stirred for 10 min, ultrasonic treatment was performed for 15 min, and then 0.018 mol of diene methacrylate and 2.2 g of 30 wt% hydrogen peroxide were slowly added, and the temperature was raised to 40° C., stirred for reaction for 20 h, and then 200 mL of deionized water was added and stirred for 15 min, filtered, washed, and dried to obtain terminal double-bond lignin;

[0046] Step A3, under nitrogen conditions, 1.2 g of terminal double-bond lignin was evenly dispersed in 20 mL of tetrahydrofuran, and then hydrogen sulfide gas was slowly introduced, and the reaction was carried out at 50° C. for 1.5 days, and then filtered, washed, and dried to obtain modified lignin;

[0047] Step A4: 35 g of modified lignin, 10 g of diatomaceous earth and 7.5 g of hydrotalcite were mixed and ground, and then 3.5 g of silane coupling agent KH560, 20 mL of deionized water and 180 mL of ethanol were added, mixed and stirred at 40° C. for 3 h, allowed to stand for 2 h, filtered and dried to obtain a reinforced filler.

[0048] The composite aerogel is prepared by the following steps:

[0049] Step B1, slowly add 100 mL of acryloyl chloride solution to 100 mL of 2,4-dihydroxybenzophenone solution in an ice water bath, and stir continuously for 7 minutes, then heat to room temperature, stir and react for 5 hours, then add 200 mL of deionized water for washing and separation, rotary evaporate to 50 mL, then add 50 mL of methanol and stir for 10 minutes, then rotary evaporate to 50 mL, stand for 24 hours, filter, and redisperse the filter cake in 50 mL of dichloromethane, then add 200 mL of petroleum ether and stir vigorously for 15 minutes, filter, and dry to obtain a terminal double bond product. The acryloyl chloride solution is prepared by mixing acryloyl chloride and dichloromethane in a dosage ratio of 0.2 mol: 100 mL, and the 2,4-dihydroxybenzophenone solution is prepared by mixing 2,4-dihydroxybenzophenone, triethylamine and dichloromethane in a dosage ratio of 0.1 mol: 0.2 mol: 100 mL;

[0050] Step B2, under nitrogen conditions, 7.02 mL of KH550 was evenly dispersed in 10 mL of methanol, 8.4 g of the terminal double bond product was slowly added, and stirred at room temperature for 30 min, and then the mixture was kept in a 25° C. oil bath for 4 h, and distilled under reduced pressure to obtain the grafted modified silane;

[0051] Step B3, 4.5g of grafted modified silane and 2mL of KH550 were dispersed in 20mL of ethanol, recorded as solution A; 16.5mL of tetraethyl orthosilicate was dispersed in 20mL of ethanol, and the pH of the solution was adjusted to 2.5, 20mL of solution A was slowly added dropwise, stirred at room temperature for 10h, the pH of the system was adjusted to 7.5, and after vigorous stirring for 7min, it was transferred to a mold and allowed to stand to form a gel, and then aged for 12h, washed, and freeze-dried to obtain a composite aerogel.

[0052] Example 3: The reinforcing filler is prepared by the following steps:

[0053] Step A1, 0.2 mol of methacrylic acid and 0.021 mol of 1,6-heptadien-4-ol were mixed and stirred uniformly, 0.86 g of 98 wt% concentrated sulfuric acid was added, and the temperature was raised to 80° C., and the mixture was reacted at a pressure of 0.3 MPa for 4.5 h, and the mixture was distilled under reduced pressure, cooled, and filtered to obtain diene methacrylate;

[0054] Step A2, 6.2 g of calcium chloride was evenly dispersed in 200 mL of dimethyl sulfoxide, 10 g of enzymatic lignin was added and stirred for 10 min, ultrasonic treatment was performed for 15 min, and then 0.024 mol of diene methacrylate and 3 g of 30 wt% hydrogen peroxide were slowly added, and the temperature was raised to 45 ° C. and stirred for 24 h, and then 200 mL of deionized water was added and stirred for 20 min, filtered, washed, and dried to obtain terminal double bond lignin;

[0055] Step A3, under nitrogen conditions, 2 g of terminal double-bond lignin was evenly dispersed in 20 mL of tetrahydrofuran, and then hydrogen sulfide gas was slowly introduced, and the mixture was reacted at 55° C. for 2 days, filtered, washed, and dried to obtain modified lignin;

[0056] Step A4: 50 g of modified lignin, 15 g of diatomaceous earth and 10 g of hydrotalcite were mixed and ground, and then 5 g of silane coupling agent KH570, 20 mL of deionized water and 180 mL of ethanol were added, mixed and stirred at 45° C. for 4 h, allowed to stand for 2 h, filtered and dried to obtain a reinforced filler.

[0057] The composite aerogel is prepared by the following steps:

[0058] Step B1, slowly add 100 mL of acryloyl chloride solution to 100 mL of 2,4-dihydroxybenzophenone solution in an ice water bath, and stir continuously for 10 min, then heat to room temperature, stir and react for 6 h, then add 200 mL of deionized water for washing and separation, rotary evaporate to 50 mL, then add 50 mL of methanol and stir for 10 min, then rotary evaporate to 50 mL, let stand for 24 h, filter, redisperse the filter cake in 50 mL of dichloromethane, then add 200 mL of petroleum ether and stir vigorously for 20 min, filter, and dry to obtain a terminal double bond product, the acryloyl chloride solution is prepared by mixing acryloyl chloride and dichloromethane in a dosage ratio of 0.3 mol: 100 mL, and the 2,4-dihydroxybenzophenone solution is prepared by mixing 2,4-dihydroxybenzophenone, triethylamine and dichloromethane in a dosage ratio of 0.2 mol: 0.3 mol: 100 mL;

[0059] Step B2, under nitrogen conditions, 9.37 mL of KH550 was evenly dispersed in 10 mL of methanol, 11.2 g of the terminal double bond product was slowly added, and stirred at room temperature for 30 min, and then the mixture was kept in a 25° C. oil bath for 4.5 h, and distilled under reduced pressure to obtain the grafted modified silane;

[0060] Step B3, 6 g of grafted modified silane and 2.5 mL of KH550 were dispersed in 20 mL of ethanol, recorded as solution A; 22 mL of tetraethyl orthosilicate was dispersed in 20 mL of ethanol, and the pH of the solution was adjusted to 3, 20 mL of solution A was slowly added dropwise, stirred at room temperature for 12 h, the pH of the system was adjusted to 8, and after vigorous stirring for 10 min, it was transferred to a mold and allowed to stand to form a gel, and then aged for 12 h, washed, and freeze-dried to obtain a composite aerogel.

[0061] Embodiment 4: A method for preparing a crack-resistant asphalt concrete material comprises the following steps:

[0062] 8 parts of asphalt, 60 parts of coarse aggregate, 25 parts of fine aggregate, 5 parts of fly ash, 5 parts of reinforcing filler prepared in Example 1, and 3 parts of composite aerogel prepared in Example 1;

[0063] Step S1, weighing raw materials by weight, mixing and stirring the coarse aggregate, fine aggregate, fly ash and the reinforcing filler prepared in Example 1 to obtain a mixed dry material;

[0064] Step S2, heating the asphalt to 140° C., continuously stirring, and sequentially adding the mixed dry materials and the composite aerogel prepared in Example 1, and mixing them evenly to obtain the anti-cracking asphalt concrete material.

[0065] Embodiment 5: A method for preparing a crack-resistant asphalt concrete material comprises the following steps:

[0066] 12 parts of asphalt, 70 parts of coarse aggregate, 35 parts of fine aggregate, 7 parts of fly ash, 8 parts of reinforcing filler prepared in Example 2, and 5 parts of composite aerogel prepared in Example 2;

[0067] Step S1, weighing raw materials by weight, mixing and stirring the coarse aggregate, fine aggregate, fly ash and the reinforcing filler prepared in Example 2 to obtain a mixed dry material;

[0068] Step S2, heating the asphalt to 155° C., continuously stirring, and sequentially adding the mixed dry materials and the composite aerogel prepared in Example 2, and mixing them evenly to obtain the anti-cracking asphalt concrete material.

[0069] Embodiment 6: A method for preparing a crack-resistant asphalt concrete material comprises the following steps:

[0070] 16 parts of asphalt, 80 parts of coarse aggregate, 45 parts of fine aggregate, 9 parts of fly ash, 12 parts of reinforcing filler prepared in Example 3, and 7 parts of composite aerogel prepared in Example 3;

[0071] Step S1, weighing raw materials by weight, mixing and stirring the coarse aggregate, fine aggregate, fly ash and the reinforcing filler prepared in Example 3 to obtain a mixed dry material;

[0072] Step S2, heating the asphalt to 170° C., stirring continuously, and sequentially adding the mixed dry materials and the composite aerogel prepared in Example 3, and mixing evenly to obtain the anti-cracking asphalt concrete material.

[0073] Comparative Example 1: This comparative example is an asphalt concrete material. The difference from Example 5 is that diatomaceous earth is used instead of the reinforcing filler prepared in Example 2, and the rest is the same.

[0074] Comparative Example 2: This comparative example is an asphalt concrete material. The difference from Example 5 is that silica aerogel is used instead of the composite aerogel prepared in Example 2, and the rest is the same.

[0075] The asphalt concrete materials prepared in Examples 4-6 and Comparative Examples 1-2 were poured into a mold, compacted at 2.0 MPa, and naturally cured for 7 days. Samples were taken according to JTG E20-2011 standard and Marshall stability test, rutting test and freeze-thaw splitting test were performed for performance test. The cured samples were placed in a UV aging box with an UV intensity of 210 W / m 2 , the aging temperature is 60℃, the aging time is 6 days, and then the freeze-thaw splitting test is carried out. The test results are shown in Table 1:

[0076] Table 1: Performance test results

[0077]

[0078] As can be seen from Table 1, the asphalt concrete material prepared by the present invention, after Marshall stability test, rutting test and freeze-thaw splitting test, has a Marshall stability in the range of (10.76-11.69) kN, a dynamic stability in the range of (6734-7021) times / mm, and a freeze-thaw splitting residual strength ratio in the range of (92.24-94.68)%, indicating that the asphalt concrete material has excellent crack resistance, UV resistance and service life.

[0079] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A crack-resistant asphalt concrete material, characterized in that: The material comprises the following raw materials in parts by weight: 8-16 parts of asphalt, 60-80 parts of coarse aggregate, 25-45 parts of fine aggregate, 5-9 parts of fly ash, 5-12 parts of reinforcing filler, and 3-7 parts of composite aerogel; The reinforcing filler is prepared by the following steps: Step A1, methacrylic acid and 1,6-heptadien-4-ol are mixed and stirred uniformly, 98 wt% concentrated sulfuric acid is added, and the temperature is raised to 60-80° C., and the reaction is carried out at a pressure of 0.2-0.3 MPa for 2.5-4.5 hours, and vacuum distillation, cooling, and filtering are performed to obtain diene methacrylate; Step A2, calcium chloride is evenly dispersed in dimethyl sulfoxide, and enzymatic lignin is added and stirred for 10 minutes, ultrasonic treatment is performed for 15 minutes, and then diene methacrylate and 30 wt% hydrogen peroxide are slowly added, and the temperature is raised to 35-45° C., and the reaction is stirred for 16-24 hours, and then deionized water is added and stirred for 10-20 minutes, and filtered, washed, and dried to obtain terminal double-bond lignin; Step A3, under nitrogen conditions, disperse the terminal double-bond lignin in tetrahydrofuran evenly, then slowly introduce hydrogen sulfide gas, react at 45-55° C. for 1-2 days, filter, wash, and dry to obtain modified lignin; Step A4: Mix the modified lignin, diatomaceous earth and hydrotalcite and grind them, then add silane coupling agent, deionized water and ethanol, stir the mixture at 35-45° C. for 2-4 hours, let stand for 2 hours, filter and dry to obtain a reinforced filler.

2. The anti-cracking asphalt concrete material according to claim 1, characterized in that: In step A1, the usage ratio of methacrylic acid, 1,6-heptadien-4-ol and concentrated sulfuric acid is 0.1-0.2 mol: 0.105-0.021 mol: 0.43-0.86 g.

3. The anti-cracking asphalt concrete material according to claim 1, characterized in that: In step A2, the usage ratio of calcium chloride, dimethyl sulfoxide, enzymatic lignin, diene methacrylate, hydrogen peroxide and deionized water is 3.1-6.2 g: 200 mL: 5-10 g: 0.012-0.024 mol: 1.5-3 g: 200 mL.

4. The anti-cracking asphalt concrete material according to claim 1, characterized in that: In step A3, the usage ratio of terminal double bond lignin and tetrahydrofuran is 0.5-2 g:20 mL.

5. The anti-cracking asphalt concrete material according to claim 1, characterized in that: In step A4, the usage ratio of modified lignin, diatomaceous earth, hydrotalcite, silane coupling agent, deionized water and ethanol is 20-50 g: 5-15 g: 5-10 g: 2-5 g: 20 mL: 180 mL.

6. The anti-cracking asphalt concrete material according to claim 1, characterized in that: The composite aerogel is prepared by the following steps: Step B1, slowly add the 2,4-dihydroxybenzophenone solution to the acryloyl chloride solution in an ice water bath, and stir continuously for 5-10 minutes, then warm to room temperature, stir and react for 4-6 hours, then add deionized water for washing, separate the liquid, rotary evaporate to 50 mL, then add methanol and stir for 10 minutes, then rotary evaporate to 50 mL, let stand for 24 hours, filter, redisperse the filter cake in dichloromethane, then add petroleum ether and stir vigorously for 10-20 minutes, filter, and dry to obtain a terminal double bond product; Step B2, under nitrogen conditions, KH550 is evenly dispersed in methanol, the terminal double bond product is slowly added, and stirred at room temperature for 30 minutes, and then the reaction is carried out in a 25°C oil bath at a constant temperature for 3.5-4.5 hours, and the mixture is distilled under reduced pressure to obtain the grafted modified silane; Step B3, dispersing the grafted modified silane and KH550 in ethanol, recorded as solution A; dispersing tetraethyl orthosilicate in ethanol, and adjusting the pH of the solution to 2-3, slowly adding solution A, stirring at room temperature for 8-12 hours, adjusting the pH of the system to 7-8, vigorously stirring for 5-10 minutes, transferring to a mold and standing to form a gel, then aging for 12 hours, washing, and freeze-drying to obtain a composite aerogel.

7. The anti-cracking asphalt concrete material according to claim 6, characterized in that: In step B1, the amount ratio of acryloyl chloride solution, 2,4-dihydroxybenzophenone solution, deionized water, methanol, dichloromethane and petroleum ether is 100mL: 100mL: 200mL: 50mL: 50mL: 200mL, the acryloyl chloride solution is prepared by mixing acryloyl chloride and dichloromethane in a dosage ratio of 0.1-0.3mol: 100mL, and the 2,4-dihydroxybenzophenone solution is prepared by mixing 2,4-dihydroxybenzophenone, triethylamine and dichloromethane in a dosage ratio of 0.05-0.2mol: 0.1-0.3mol: 100mL.

8. The anti-cracking asphalt concrete material according to claim 6, characterized in that: In step B2, the usage ratio of KH550, methanol and terminal double bond product is 4.68-9.37 mL:10 mL:5.6-11.2 g.

9. The anti-cracking asphalt concrete material according to claim 6, characterized in that: In step B3, the usage ratio of tetraethyl orthosilicate, ethanol and solution A is 11-22 mL: 20 mL: 20 mL, and the usage ratio of grafted modified silane, KH550 and ethanol in solution A is 3-6 g: 1.5-2.5 mL: 20 mL.

10. A method for preparing the anti-cracking asphalt concrete material according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step S1, weighing raw materials by weight, mixing and stirring the coarse aggregate, fine aggregate, fly ash and reinforcing filler to obtain a mixed dry material; Step S2, heating the asphalt to 140-170° C., stirring continuously, and sequentially adding the mixed dry materials and the composite aerogel, mixing evenly, to obtain the anti-cracking asphalt concrete material.

Citation Information

Patent Citations

  • Composite asphalt mixture suitable for high-latitude or high-altitude area

    CN108484001A

  • Asphalt mixture capable of relieving urban heat island effect

    CN108727840A

  • Purification type recycled asphalt concrete and preparation process thereof

    CN109650783A

  • Recycled asphalt concrete and preparation method thereof

    CN113666668A

  • Multifunctional asphalt modifier and preparation method thereof

    CN118852734A

Cited By

  • Pavement crack regeneration grouting repair material and preparation method thereof

    CN120247463A

  • Asphalt concrete prepared from modified steel slag, iron tailings and straw and preparation method of asphalt concrete

    CN120647217A

  • Modified steel slag cooperates with iron tailings and straw asphalt concrete and preparation method

    CN120647217B